2015
DOI: 10.1038/srep15202
|View full text |Cite
|
Sign up to set email alerts
|

Evolution and Function of Dinosaur Teeth at Ultramicrostructural Level Revealed Using Synchrotron Transmission X-ray Microscopy

Abstract: The relationship between tooth form and dietary preference is a crucial issue in vertebrate evolution. However, the mechanical properties of a tooth are influenced not only by its shape but also by its internal structure. Here, we use synchrotron transmission X-ray microscopy to examine the internal microstructures of multiple dinosaur teeth within a phylogenetic framework. We found that the internal microstructures of saurischian teeth are very different from advanced ornithischian teeth, reflecting differenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(50 citation statements)
references
References 35 publications
(39 reference statements)
2
47
1
Order By: Relevance
“…tion. On the other hand, crown ornamentations (CI of 0.49) and microstructure (CI of 0.62), although bearing functional properties and linked to diet (e.g., Sander, 1999;Brink et al, 2015Brink et al, , 2016Wang et al, 2015), are the least homoplastic possibly because they require more complex developmental/genetic mechanisms to evolve than other dental features under the same evolutionary pressure. Indeed, crown microstructure has been suggested to bear some phylogenetic potential in dinosaurs (Hwang, 2005(Hwang, , 2010Wang et al, 2015).…”
Section: Taxonomic Potential Of Theropod Teethmentioning
confidence: 99%
“…tion. On the other hand, crown ornamentations (CI of 0.49) and microstructure (CI of 0.62), although bearing functional properties and linked to diet (e.g., Sander, 1999;Brink et al, 2015Brink et al, , 2016Wang et al, 2015), are the least homoplastic possibly because they require more complex developmental/genetic mechanisms to evolve than other dental features under the same evolutionary pressure. Indeed, crown microstructure has been suggested to bear some phylogenetic potential in dinosaurs (Hwang, 2005(Hwang, , 2010Wang et al, 2015).…”
Section: Taxonomic Potential Of Theropod Teethmentioning
confidence: 99%
“…The adaptive changes in internal tooth structure related to a shift in feeding ecology during this critical transition are not fully understood, despite a few studies focusing on non-avian dinosaurs that are distantly related to avialans [4,12]. Here we report the ultramicrostructural details in enantiornithines, ornithuromorphs, non-ornithothoracine avialans, and non-avian paravian theropods (microraptorines and troodontid dinosaurs) using both scanning electron microscopy (SEM) and synchrotron transmission X-ray microscopy (TXM) [13]. We found similar tooth microstructure between one Microraptor species and other Early Cretaceous birds.…”
Section: Introductionmentioning
confidence: 99%
“…We found similar tooth microstructure between one Microraptor species and other Early Cretaceous birds. The lack of mantle dentin with interglobular porous spaces (IGS) between the enamel and orthodentin [13,14] in avialans indicates a derived condition in Saurischian dinosaurs. In addition, the internal ultramicrostructure of teeth provides further evidence for divergent feeding ecology or food acquisition and processing in birds and closely related paravians.…”
Section: Introductionmentioning
confidence: 99%
“…Experiments performed on bovine teeth showed that crack arresting occurs in DEJ only when the crack initiation takes place in enamel region [44]. Other studies [45] discussed the importance of the region between DEJ and dentin, the inter-globular porous space (IGS), in crack deflection and energy absorption during crack propagation [44].…”
Section: Accepted Manuscriptmentioning
confidence: 99%